Epigenetics and Environmental Roles: The Reality of Igbo-Jewish Link - Oguejiofor, Omeje Oguejiofor; Ezeugwu , Cindy Anene (South Asian Journal of Social Sciences and Humanities, 2020)
This paper aims to examine the Igbo-Jewish link which has received scant attention in  scholarly discourse. Among the few major critical submissions is that Igbos of the South  Eastern part of Nigeria, originated from Israel in one way or the other. Prominent among  these claims is that Igbos are one of the lost tribes of Israel’ and the ‘Hametic race saga’. Epigenetic and Mythological theories will be useful in helping to explain the Igbo history,  origin, migration and colour change. Findings show that proponents of Igbo-Jewish link have  not to the best of the researchers’ knowledge, given a satisfactory explanation for the difference in the Igbo-Israeli skin colour, neither have they addressed in what period of history that the Jews migrated to Igbo land. The paper, therefore, attempts to change the old  narratives which support the erroneous claim that Igbos originated from Israel by briefly  tracing their correct origin with a view to lay to rest, the myths and speculations surrounding  their identity. Much of what drives man to develop self and leave a significant mark in his  society is the quest to identify with his true origin and in Africa today, the idea of  westernization have affected the art of storytelling and indigenous documentation which has  been an ageless tradition. Some Africans, based on their understanding view this as waste of  time or impacting orchestrated stories in the minds of indigenes’ hence, they prefer westernized format of aligning with the Eurocentric view about the origin of the Igbos. The  study concludes that if any one group came from the other, it would be the Jews who  migrated from the much older Igbo race and not the other way around.
Keywords: Igbos; Jew; Israel; Epigenetic; Migration; Translocation; History; Origin